Perancangan Dan Implementasi Sistem Informasi Terintegrasi Desa Madukoro Baru Berbasis Website - Refilia Sari; Hartono (Jurnal Sains Informatika Terapan, 2026)
This study focuses on the development of an Integrated Village Information System for Madukoro Baru Village, Kotabumi District, North Lampung Regency, aimed at enhancing public service efficiency and information dissemination. Despite the village's significant human and natural resources, current communication relies heavily on face-to-face meetings, leading to information gaps. To address these issues, a web-based system was designed using React, Express, Tailwind CSS, and MariaDB. The system was developed and tested using a comprehensive dataset comprising over 500 population records, 10+ village asset entries, and 12 months of historical administrative logs. It integrates six core modules: population administration, village asset management, news, event agendas, statistics, and complaints. Data collection utilized primary sources (interviews and observations) and secondary sources (official village documents). The development adopted a hybrid methodology combining Rapid Application Development (RAD) and Waterfall approaches. Black-box testing validated that all modules function correctly according to planned scenarios. Implementation results demonstrate that this system, capable of processing real-time data for over 1,000 residents, facilitates transparent access to information and streamlines administrative processes. This study presents a scalable digital platform that bridges the gap between manual processes and modern e-governance.